Doxing: The Sandy Hook Case Study - Daria Bulgakova (Наукові записки НаУКМА: Юридичні науки)
This article aims to contribute to the doxing problem concerning the interpretation of this phenomenon and the provision of anti-doxing measures. The author argues that doxing is a social practice of searching and disclosing adverse events and party information on the internet and is based on people’s original intention of justice to let the public understand the facts and truth. However, doxing can influence online audience behavior and shift the results of public opinion polls. The case study on Sandy Hook aims to illustrate doxing and highlights the value of sifting through the information that people receive from various sources. The research exemplifies the negative consequences of doxing, particularly for the victims, whose children were tragically killed, as conspiracy theorist Alex Jones exacerbated the situation by portraying the Sandy Hook shooting as a hoax. Thus, the author suggests the adoption of cyber liability policies and the implementation of cyber insurance to mitigate the risks of doxing. Such measures can also help protect individuals from the potential harm caused by the destructive practice of unregulated media and internet exposure. It is important because, considering the factors of the case study, the coverage of doxing is also shaped by a multifaceted discourse encompassing identity theft, armed conflicts, political issues, cyber trolling, ethical dilemmas in media practices, public health implications, and even social inequality. This discourse has not only sustained the initial wave in the scope of defamation but also plays a key role in studying the evolution of doxing and shaping its understanding among readers.